2019
DOI: 10.1007/s11356-019-04885-w
|View full text |Cite
|
Sign up to set email alerts
|

Associations between microplastic pollution and land use in urban wetland sediments

Abstract: Microplastic pollution is concerning because it is widespread in aquatic environments and there is growing evidence of negative biological effects. Here, we present one of the first studies to examine microplastic pollution (plastic particles <1 mm) in urban wetlands and investigate relationships between contamination and urban land use. Sediment samples were collected from twenty independent urban wetlands, each with different types of urban land use within their catchments. Microplastics were observed at all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(45 citation statements)
references
References 50 publications
4
39
2
Order By: Relevance
“…High density of HDPE in surface water is related to the population density factors as estimated by the model. The contributions of population density on plastic litter is in accordance with other results from Chesapeake Bay (Yonkos et al 2014), Great Lakes (Baldwin et al 2016), and urban wetlands (Townsend et al 2019). Combined with the anthropogenic activities, population density will contribute more in increasing plastic quantities (Best 2019).…”
Section: Discussionsupporting
confidence: 89%
“…High density of HDPE in surface water is related to the population density factors as estimated by the model. The contributions of population density on plastic litter is in accordance with other results from Chesapeake Bay (Yonkos et al 2014), Great Lakes (Baldwin et al 2016), and urban wetlands (Townsend et al 2019). Combined with the anthropogenic activities, population density will contribute more in increasing plastic quantities (Best 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Although it is corrosive and harmful, recycling and washing could address this issue. The experimental recovery data show that the separation effect is better than that of NaCl solution obviously [54,93,[102][103][104]. In addition, CaCl 2 solution (1.5 g/cm 3 ) is used for separation tests based on its eco-friendliness, density, and low cost [105].…”
Section: Suspensionmentioning
confidence: 99%
“…Many fresh water sediments are contaminated with microplastics, especially in areas near plastic waste sources. Sediment samples from 20 different urban wetlands were analyzed by Townsend et al and showed a strong correlation between microplastic abundance and industrial land use (Townsend et al 2019). The study by Horton et al analyzed sediment from the tributaries of the River Thames, UK.…”
Section: Sources and Presence Of Microplastics In Sedimentmentioning
confidence: 99%